2016
DOI: 10.1080/10826068.2015.1015561
|View full text |Cite
|
Sign up to set email alerts
|

High-yield production of lipoglycopeptide antibiotic A40926 using a mutant strain Nonomuraea sp. DP-13 in optimized medium

Abstract: The lipoglycopeptide antibiotic A40926 produced by Nonomuraea sp. is a complex of structurally related components differing in the fatty acid moiety. Besides showing an intrinsic antibacterial activity, A40926 is the precursor of the semisynthetic antibiotic Dalvance. In this work, A40926 production by a mutant strain Nonomuraea sp. DP-13 was investigated. It was found that A40926 production was markedly promoted by using poorly assimilated carbon source maltodextrin and nitrogen source soybean meal. Addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Both mycelium growth and metabolite accumulation are affected by the composition of the fermentation medium (Chen et al 2015; Huang et al 2018). In single-factor experiments, we found that starch and oil as carbon sources and peanut meal as a nitrogen source can stably provide nutrients and energy for microbial growth and ascomycin production.…”
Section: Discussionmentioning
confidence: 99%
“…Both mycelium growth and metabolite accumulation are affected by the composition of the fermentation medium (Chen et al 2015; Huang et al 2018). In single-factor experiments, we found that starch and oil as carbon sources and peanut meal as a nitrogen source can stably provide nutrients and energy for microbial growth and ascomycin production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cu 2+ stimulated A40926 biosynthesis while Co 2+ showed an inhibitory effect. As shown for valine, even l -leucine addition led to an increased production of total A40926 and changed the complex toward the B 0 compound ( Figure 4 ) [ 20 ]. While the shift in complex composition after amino acid addition can be easily rationalized, there are currently no clues as to why certain carbon sources and metal ions stimulate or inhibit growth and/or A40926 production.…”
Section: Improvement Of A40926 Productionmentioning
confidence: 98%
“…This group also con rmed that the addition of L-leucine could improve A40926 production. Other studies con rmed that the addition of branchedchain amino acids promotes the production of A40926 and teicoplanin (Chen et al 2016).…”
Section: Introductionmentioning
confidence: 94%
“…The authors declare that they have no con ict of interest. (Jovetic et al 2008); c, (Chen et al 2016);d, (Yan L 2013); e, (Liu ZY 2018); f, (Huang LL 2012); g, (Marcone et al 2014); h, (Chen CF 2015). The recombinant plasmid pIJ8660-Pgapdh-dbv3-Pgapdh-dbv20 (A), PCR veri cation (B), and fermentation assay of the different strains (C).…”
Section: Declarations Con Ict Of Interest Statementmentioning
confidence: 99%